Serum Angiotensin-Converting Enzyme Has a High Negative Predictive Value in the Investigation for Systemic Sarcoidosis - Niederer, Rachael L.; Al-Janabi, Ahmed; Lightman, Sue L.; Tomkins-Netzer, Oren (American journal of ophthalmology, 2018)
To examine whether measurement of serum angiotensin-converting enzyme (ACE) is useful in diagnosing sarcoidosis in undifferentiated uveitis. Evaluation of a diagnostic test. Data collection was performed from 1035 consecutive subjects presenting with uveitis to Moorfields Eye Hospital undergoing measurement of serum ACE as part of baseline investigations for underlying systemic disease. The main outcome measures were sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of elevated serum ACE. Mean age of the sample was 41.7 years and 56.1% of subjects were female. Sarcoidosis was the underlying cause for the uveitis in 110 subjects (10.6%) and was more common in adults, female subjects, black subjects, and subjects with intermediate uveitis or panuveitis. ACE was elevated in 196 subjects (18.9%) and elevated levels were observed in 85 subjects eventually diagnosed with underlying sarcoidosis (true positive 77.3%) and in 111 subjects with an alternate diagnosis (false positive 12.0%). In adult subjects, sensitivity of serum ACE was 78.1%, specificity 90.0%, and PPV 43.6%, but the NPV was 97.0%. The test performed well, with area under curve (AUC) 0.897 (95% confidence interval [CI] 0.854–0.941). Serum ACE performed less well in distinguishing sarcoid uveitis in pediatric subjects, with sensitivity 60.0%, specificity 78.5%, and PPV 10.0%, but again NPV was high at 96.9% and AUC was 0.828 (95% CI 0.571–1.000). Serum ACE had a very high negative predictive value for sarcoid uveitis, eliminating the need for further screening tests in subjects with normal serum ACE, unless clinical suspicion was high. •A total of 10.6% of subjects with undifferentiated uveitis were diagnosed with sarcoidosis.•Serum angiotensin-converting enzyme (ACE) had a very high negative predictive value for sarcoid uveitis.•Normal serum ACE obviates further investigations for sarcoid in most patients.•Positive predictive value was higher in intermediate uveitis or panuveitis.